Well-being and perspective of second year MBBS students on online pharmacology classes held during COVID-19 pandemic in a tertiary care teaching hospital - Kamath, Latha; S., Nishith R.; Chakraborty, Ananya (International Journal of Basic & Clinical Pharmacology, 2021)
Background: COVID-19 pandemic shifted all the classroom teaching to virtual online platforms. The overnight change in the teaching structure posed serious challenges especially for medical education. This study aims to assess the well-being of medical students undergoing online medical education during COVID-19 pandemic and their perspective on online pharmacology classes. Methods: World health organization (WHO-5) well-being index was used to assess well-being of students. An internally validated questionnaire was used to assess student’s perspective on online pharmacology classes. The questionnaire was administered to eligible consenting students online through Google forms. The data obtained was analysed by SPSS software. Results: The mean wellness score (%) for all participants, (n=118) was 48.87%. The mean wellness score for males (58.67%) was higher than for females (42.41%). The average score for overall benefit of conducting online pharmacology classes was 3.32 out of 5. Objectively assessed online interactions like formative assessment, polls and quiz were rated higher than subjective interactions like debate. Conclusions: COVID-19 pandemic has caused massive disruption in the life of many people. In our study, we report a decreased well-being score in medical students attending virtual classes. The findings on well-being of students have implications on planning redressal mechanism in such extreme situations. Our analysis of student’s perspective about online interactions has implications beyond online classes. Some of the interactions can be instituted into regular curriculum increasing the student’s participation.